Analisis Pengaruh Kinerja Keuangan Terhadap Harga Saham pada Perusahaan Pertambangan yang Terdaftar di Bursa Efek Indonesia (BEI) Periode 2019-2022 - Ika Soleha; Anisa Indah Mutiasari; Anggit Dyah Kusumastuti (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2024)
This study aims to determine the effect of financial performance as measured by the current financial ratio, return on equity, debt to equity ratio, and earning per share on stock prices. The population of this study are mining companies listed on the IDX with an observation period of 2019-2022. The sample of this study used purposive sampling method. The type of research used is explanatory research with a quantitative approach. The results of this study indicate that partially the earning per share variable has a significant effect on stock prices, while the CR, ROE, and DER variables have no effect. Simultaneously, it shows that the four variables, namely CR, ROE, DER, and EPS, have a significant effect on stock prices. This research is supported by an R2 value of 42.4%.